Contesting the Space in Indonesia: A Case From Al-Washliyah in North Sumatra - Faisal Riza (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2014)
In the atermath of the Reform movement in 1998, Indonesia has bagun to face significant changes such as an increase in the degree of democratization through decentralization. Since 1998, there have been four general elections (1999, 2004, 2009) conducted in Indonesia. These elections include a presidential election by Legislative Assembly (1999), direct presidential elections (2004 and 2009), and elections of local government heads (Pilkada) in Indonesia’s provinces, districts, and municipalities. Under these circumstances, Islamic civil society organizations are and have often been placed in the crossroad of the local politics. Al- Washliyah, the biggest Islamic organization in North Sumatra, is not an exception. It has played a very profound role in local development in which political engagement has been unavoidable. There are many members of Al-Washliyah who works in political parties with various ideologies. Politicians often request Al- Washliyah support especially in moments of Pilkada (regional election). This article focuses on the strategies of Al-Washliyah in development of democratization in North Sumatra, analyzing its moves, involvement, and the use of their organi zation in the electoral politics. It explains the transformation of Al- Washliyah from cultural politics to practical politics in which Al- Washliyah acts much like a political party. Keyword: Al-Washliyah, decentralization, general election, political Islam